A strategic management paper for Consolidated Orix Leasing & Finance Corporation - Perucho, Sheila P. (Animo Repository, 1998)
In the world of business, competition is commonplace. Companies arm themselves with strategies in order to survive, or better yet, dictate the terms of competition. The financial services industry is one of the oldest yet most stable industries. At the forefront of which is ORIX Corporation of Japan. From a leasing firm, it has built itself up to become a diversified, multinational company. In the 1960s, it formed a joint venture with Solidbank Corporation to bring the concept of leasing into the Philippines through the birth of what is now known as Consolidated ORIX Leasing and Finance Corporation. As an affiliate of ORIX Corporation of Japan and Solidbank Corporation, the company acts as their leasing arm in the financial services industry in the country.